Isolation and characterization of Salmonella phages for controlling bacterial infections - Mirmiran, Seyyed Danial; Li, Xinxin; Li, Xiangmin; Qian, Ping (Frontiers in Veterinary Science, 2025)
IntroductionThe rise of multidrug-resistant (MDR) Salmonella enterica poses a significant threat to public health, veterinary medicine, and food safety. Bacteriophages offer a promising alternative to antibiotics due to their host specificity and ability to lyse bacteria without disrupting commensal microbiota.MethodsIn this study, twelve Salmonella-specific phages were isolated from diverse environmental sources across China. Specifically, DN01 originated from livestock manure in Shanxi Province (Northwest China), DN03 from poultry wastewater in Suizhou, Hubei Province (Central China), DN19 from slaughterhouse effluent in Guangdong Province (South China), and DN28 from hospital sewage in Zhejiang Province (Eastern China). This geographic and ecological diversity underscores the broad natural distribution of Salmonella phages, providing a representative foundation for subsequent morphological, genomic, and therapeutic analyses. The host bacterium Salmonella Enteritidis SE006, was used for phage propagation. Four lytic phages, which exhibited broad host ranges, were selected for in-depth characterization. Their biological properties, including optimal multiplicity of infection (MOI), latent period, burst size, pH, and thermal stability, and anti-biofilm activity, were systematically evaluated. Morphology was analyzed via transmission electron microscopy (TEM), and whole-genome sequencing, functional annotation, and phylogenetic analysis were conducted to assess genetic safety and taxonomic placement.ResultsAll phages exhibited potent lytic activity across multiple Salmonella serovars, including MDR strains, with MOIs as low as 0.00001 and short latent periods (10–20 min). They remained stable over a broad pH range (3–11) and exhibited thermal stability from 4 °C up to 50 °C, with partial loss of activity observed at 60 °C for some phages. Genomes ranged from 5,563 to 86,377 bp and lacked genes related to lysogeny, virulence, or antibiotic resistance. TEM and phylogenetic analyses classified the phages within distinct families of the Caudoviricetes class. In vitro assays demonstrated significant inhibition of bacterial growth and disruption of mature biofilms. Phage treatment significantly improved the survival of S. Enteritidis-infected mice over a 12-day period., survival rates were 0% (PBS), 25% (DN01), 33% (DN03), 75% (DN19), 85% (DN28), and 100% (cocktail).ConclusionThese results highlight the promise of DN01, DN03, DN19, and DN28, particularly in cocktail form, as safe, stable, and effective agents for phage-based control of multidrug-resistant Salmonella enterica.